Media sosial sebagai panggung baru public relations: Peluang dan tantangan - Mashudi, Fajar Asnif (Maliki Interdisciplinary Journal, 2024)
The rapid development of digital technology has changed the public relations landscape significantly. Social media has become a key platform for organizations to communicate with the public, build brand image and manage reputation. This research aims to analyze the opportunities and challenges faced by public relations practitioners in utilizing social media. The research results show that social media offers a number of opportunities, such as wider audience reach, more personalized interactions, and the ability to get real-time feedback. However, on the other hand, social media also presents challenges, including the spread of hoaxes, changes in consumer behavior, especially the millennial generation, as well as privacy and data security issues. This research concludes that social media has become a very important tool in modern public relations. However, to harness the full potential of social media, public relations practitioners need to develop a comprehensive strategy, including building relevant content, monitoring public sentiment, and managing crises quickly. Additionally, it is important for public relations practitioners to understand social media user behavior and adopt good security practices to protect an organization’s data and reputation.